Anticholinergic Drug Exposure Increases the Risk of Delirium in Older Patients Undergoing Elective Surgery - Herrmann, Matthias L.; Boden, Cindy; Maurer, Christoph; Kentischer, Felix; Mennig, Eva; Wagner, Sören; Conzelmann, Lars O.; Förstner, Bernd R.; Rapp, Michael A.; von Arnim, Christine A. F.; Denkinger, Michael; Eschweiler, Gerhard W.; et al. (Frontiers in Medicine, 2022)
Introduction: Postoperative delirium (POD) is a common and serious adverse event of surgery in older people. Because of its great impact on patients’ safety and quality of life, identification of modifiable risk factors could be useful. Although preoperative medication intake is assumed to be an important modifiable risk factor, the impact of anticholinergic drugs on the occurrence of POD seems underestimated in elective surgery. The aim of this study was to investigate the association between preoperative anticholinergic burden and POD. We hypothesized that a high preoperative anticholinergic burden is an independent, potentially modifiable predisposing and precipitating factor of POD in older people. Methods: Between November 2017 and April 2019, 1470 patients of 70 years and older undergoing elective orthopedic, general, cardiac or vascular surgery were recruited in the randomized, prospective, multicenter PAWEL trial. Anticholinergic burden of a sub-cohort of 899 patients, who did not receive a multimodal intervention for preventing POD, was assessed by two different tools at hospital admission: The established Anticholinergic Risk Scale (ARS) and the recently developed Anticholinergic Burden Score (ABS). POD was detected by confusion assessment method (CAM) and a validated post discharge medical record review. Logistic regression analyses were performed to evaluate the association between anticholinergic burden and POD. Results: POD was observed in 210 of 899 patients (23.4%). Both ARS and ABS were independently associated with POD. The association persisted after adjustment for relevant confounding factors such as age, sex, comorbidities, preoperative cognitive and physical status, number of prescribed drugs, surgery time, type of surgery and anesthesia, usage of heart-lung-machine, and treatment in intensive care unit. If a patient was taking one of the 56 drugs listed in the ABS, risk for POD was 2.7-fold higher (OR=2.74, 95% CI=1.55-4.94) and 1.5-fold higher per additional point on the ARS (OR=1.54, 95% CI=1.15-2.02). Conclusion: Preoperative anticholinergic drug exposure measured by ARS or ABS was independently associated with POD in older patients undergoing elective surgery. Therefore, identification, discontinuation or substitution of anticholinergic medication prior to surgery may be a promising approach to reduce the risk of POD in older patients.